Kajian Kritis Terhadap Strategi Reformasi Perpajakan Dalam Menyambut Era Digital - Mayasari, Risa; Narsa, I Made (E-Jurnal Akuntansi; Vol 30 No 2 (2020), 2020)
The research aims to find and uncover the challenges of implementing tax reform in the digital age and formulate suitable strategies for tax reform. This research use descriptive qualitative, which use secondary data, collected in two stages, namely: searching and collecting relevant literature, and determining categories, and analyzing data with qualitative techniques. The results of the study revealed tax reform faces an increasingly greater challenge in the digital age, which is not only the challenge of increasing the capability and integrity of the tax authority, but also the challenge of integrating various occured changes because of digitalization and the industrial revolution 4.0. So that the right strategy in implementing tax reforms in the digital era is to increase the trust and compliance of taxpayers by increasing the capability and integrity of tax authorization through the modernization of the system and controlling tax human resources. Keywords: Tax Reform; Industrial Revolution 4.0; Tax Strategy; Taxpayers Complience.